Development of a reverse transcription recombinase polymerase amplification assay for rapid detection of Theiler's murine encephalomyelitis virus. (October 2018) - Ma, Lei; Cong, Feng; Zhu, Yujun; Wu, Miaoli; Xu, Fengjiao; Huang, Ren; Moore, Robert J.; Guo, Pengju
Abstract: Theiler's murine encephalomyelitis virus (TMEV) is one of the most common viral pathogens that circulate widely in captive mouse colonies. A molecular biology detection method would be a useful tool to use in an integrated program to monitor and prevent TMEV infection and transmission. Thus, a reverse transcription recombinase polymerase amplification (RT-RPA) assay was developed to detect TMEV infection. The sensitivity of the RT-RPA assay approached 8 copies per reaction, which is equivalent to the sensitivity of RT-qPCR reactions. This assay did not detect RNA extracts from other murine pathogens included in this study or TMEV negative samples. Brain tissues and contaminated biological materials were used to assess the clinical performance of the RT-RPA. The detection results of RT-RPA and RT-qPCR were very similar, except that a contaminated biological material sample which was positive by RT-qPCR, with a CT value of 38, was negative by RT-RPA. In summary, the developed RT-RPA assay offers a rapid, sensitive and specific alternative method for monitoring of TMEV, especially in resource-limited conditions. Highlights: Real-time RT-RPA assay was successfully developed for rapid, sensitive and specific detection of TMEV. This assay has the potential to apply in a mobile laboratory for field detection. RT-RPA is more cost-effective than RT-qPCR.